Consequences of premature ovarian insufficiency on women’s sexual health - Maciejewska-Jeske, Marzena; Szeliga, Anna; Męczekalski, Błażej (Menopause Review/Przegląd Menopauzalny, 2018)
Premature ovarian insufficiency (POI) is defined by amenorrhoea and decreased serum levels of oestrogens associated with increased serum gonadotropins concentrations before the age of 40 years. Patients suffering from POI present with irregular menses, either secondary or (less common) primary amenorrhoea, and subfertility. POI affects approximately 1 in 100 women by the age 40 years and 0.1% by 30 years of age. Both spontaneous and iatrogenic causes may induce POI, although up to 90% of POI cases are idiopathic. Impairment of sexual function is a common problem affecting women suffering from POI. Premature loss of gonadal function is particularly traumatic in young women and affects many aspects of physical and social life. POI patients suffer from genital pain due to vaginal dryness and diminished sexual arousal. Additionally, POI patients report increased anxiety, depressed mood, and have impaired interactions with their peers, which leads to feeling less feminine and having decreased self-esteem. Moreover, they have significantly decreased physical and psychological well-being when compared to age-matched controls. Systemic hormonal replacement therapy and topical oestrogen therapy as well as vaginal moisturisers may be used in the treatment of POI patients’ sexual impairment.